Hiding in Plain Sight: Toward a Celebration of Hebraica Catalogers - Kohn, Roger (Judaica Librarianship, 2022)
This article offers a chance to readers to know better the Hebraica catalogers who have been active in the United States and Canada, currently active, retired and deceased. There are two parts in this article. First the author presents how the article came into being, the source the author used and the existing bibliography. Then the author presents the field of Hebraica and Judaica librarianship in the “longue durée.” The second part contains testimonies of Hebraica catalogers who accepted to contribute to this article.